2009
DOI: 10.1111/j.1467-8268.2009.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

ARV Treatment and Time Allocation to Household Tasks: Evidence from Kenya

Abstract: Using longitudinal survey data collected over a period of two years, this paper examines the impact of antiretroviral (ARV) treatment on the time allocated to various household tasks by treated HIV-positive patients and their household members. We study outcomes such as time devoted to housework, firewood and water collection, as well as care-giving and care-seeking. As treatment improves the health and productivity of patients, we find that female patients in particular are able to increase the amount of time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 17 publications
1
33
0
1
Order By: Relevance
“…In Madagascar and Benin, women spend 164 hours per year and 273 hours per year, respectively, collecting water; this corresponds to 14 and 23 hours a month, or 8.8 percent and 14.4 percent, respectively, of monthly working time (Blackden and Wodon (2006)). In Kenya, as documented by d 'Adda et al (2009), women devote 3.8 hours a week collecting water (compared to 1.3 for men), or equivalently 15.2 hours a month (compared to 5.2 hours a month for men). In Guinea, lack of access to water also imposes a very high time cost on women (Bardasi and Wodon (2009)).…”
Section: Water and Sanitationmentioning
confidence: 99%
See 2 more Smart Citations
“…In Madagascar and Benin, women spend 164 hours per year and 273 hours per year, respectively, collecting water; this corresponds to 14 and 23 hours a month, or 8.8 percent and 14.4 percent, respectively, of monthly working time (Blackden and Wodon (2006)). In Kenya, as documented by d 'Adda et al (2009), women devote 3.8 hours a week collecting water (compared to 1.3 for men), or equivalently 15.2 hours a month (compared to 5.2 hours a month for men). In Guinea, lack of access to water also imposes a very high time cost on women (Bardasi and Wodon (2009)).…”
Section: Water and Sanitationmentioning
confidence: 99%
“…For instance, Ilahi (2001) found that women living in rural Peru who rely on firewood or coal as a source of energy tend to allocate a smaller proportion of their time to self-employment activities and a greater proportion of time to housework, compared to women who use gas or electricity. In Kenya, as documented by d 'Adda et al (2009), women devote 2.7 hours a week collecting firewood (compared to 0.3 for men), in addition to the almost 4 hours a week that they spend collecting water.…”
Section: Electricitymentioning
confidence: 99%
See 1 more Smart Citation
“…ART effectively delays mortality 2 , reduces horizontal 35 and vertical 6 HIV-transmission, prevents HIV-associated tuberculosis 7 and enhances the quality of life for HIV-positive people 8 , 9 . South Africa has the largest ART programme in the world, with 83% coverage 10 .…”
Section: Introductionmentioning
confidence: 99%
“…CBT—in reducing alcohol consumption—has been identified as a method to increased ARV adherence [7173]. ARV adherence and its resulting medical and functional benefits, in turn, have been shown to increase labor force participation (LFP) [7477] and increase household productivity (HP) [78]. Thus, through a mechanism of ARV adherence, CBT can increase LFP and HP.…”
Section: Methodsmentioning
confidence: 99%